Antimicrobial activity of Etlingera elatior leaf extract in Staphylococcus aureus-induced cystitis: an in vivo study - Ridha Nirmalasari; Hujjatusnaini, Noor; Sari, Mita; Wahyuni Nurqadriyani Bustan (Universitas Muhammadiyah Purwokerto, 2026)
Background: Etlingera elatior has been reported to possess antimicrobial properties; however, its therapeutic effects in bacterial cystitis, particularly those caused by Staphylococcus aureus (S. aureus), remain inadequately explored in vivo. Objective: This study aimed to evaluate the antimicrobial and anti-inflammatory effects of Etlingera elatior leaf extract in an experimental model of S. aureus cystitis. Methods: A true experimental posttest-only design was conducted using 28 male BALB/c mice induced with S. aureus. The animals were allocated into control and treatment groups receiving Etlingera elatior leaf extract at concentrations of 40%, 50%, 60%, 70%, and 80%. Therapeutic outcomes were assessed based on urinary tract mucosal fluid secretion and bacterial colony counts. Data were analyzed using one-way ANOVA followed by post hoc testing. Results: Treatment with Etlingera elatior leaf extract significantly reduced cystitis severity compared with the infected control group (p < 0.05). The extract demonstrated both antimicrobial and anti-inflammatory effects, as indicated by reductions in bacterial load and mucosal secretion. Among the tested concentrations, the 40% extract showed the most consistent therapeutic effect, with outcomes comparable to ciprofloxacin. Conclusions: Etlingera elatior leaf extract exhibits potential as an alternative therapeutic agent for bacterial cystitis. Its antimicrobial and anti-inflammatory properties support its further development as a complementary treatment for urinary tract infections.